The St. Trudpert Song of Songs: Latin Intertextuality and German Mysticism - Dorgan, Gennifer (Journal of medieval religious cultures, 2025)
This article examines the place of the St. Trudpert Song of Songs, a twelfth-century German Song of Songs commentary, in the histories of mysticism and women's literature. Written by a cleric for an audience of nuns, the text includes Latin phrases with minimal context, inviting its female audience to grapple with the concealed mystical sense of these words. The text's author thus assigns its female audience the opportunity to make meaning out of the Latin intertexts. This is a novel development in early Middle High German literature that anticipates the construction of women's spiritual authority in later mystical texts such as the Flowing Light of the Godhead.